Evaluation of anti-ulcer activity of leaves extract of Thunbergia erecta in ethanol induced ulcer rats - SONAM PAL; MANJU PRAJAPATI; JANKI PRASAD RAI; AKHLESH KUMAR SINGHAI (International Journal of Multidisciplinary Research and Studies, 2023)
Background Peptic ulcers are erosions that affect the mucosa of the gastrointestinal tract and may extend to the muscle layer. Their formation is influenced by various factors, disrupting the mucosa's protective and offensive balance. Major contributors include Helicobacter pylori infection and non-steroidal anti-inflammatory drug (NSAID) use. Novel complementary treatments using natural products are being explored to prevent and treat ulcers. This study aims to examine the effects of Thunbergia erecta extract on rat gastric mucosa to determine if it has any anti-ulcer activity. Methods The methanolic extract of Thunbergia erecta was prepared using soxhlet apparatus techniques, and its anti-ulcer effect was tested on ethanol-induced gastric ulcer models at different doses. Results The results showed a significant reduction in the total volume of gastric juice and free acidity of gastric secretion (P < 0.01), similar to the standard drug ranitidine. Additionally, there was a noteworthy decrease in ulcer index (P < 0.01) compared to the control group. Conclusion The findings indicate that the methanolic extract of Thunbergia erecta possesses promising anti-ulcer activity in the alcohol-induced ulcer model, supporting its traditional use as claimed.